Early Onset of Atherosclerosis of The Carotid Bifurcation in Newborn Cadavers - (:unkn) unknown (PREMCHAND SHANTIDEVI RESEARCH FOUNDATION, 2016)
Introduction: The anatomy of arterial bifurcations affects blood flow and has a significant role in the development of vascular disease. Therefore, it is important to know the structural characteristics of the Common Carotid Artery (CCA) and its branches for early onset of atherosclerosis in newborns. Aim: The present study was conducted to evaluate the characteristics of CCA in newborn cadavers. Materials and Methods: Eight carotid arteries obtained from newborn cadavers were used. The outflow to inflow area ratios was calculated to evaluate vessel diameters. Additionally, scanning electron and light microscopic investigations were conducted with tissue samples. The brachial artery of each cadaver was used as controls. Correlation between area ratios and atherosclerotic endothelial damage was determined. Results: Light microscopic investigations demonstrated that control group sections showed no positivity for Oil red O staining, while carotid bifurcation regions depicted widespread occurrence of intimal lipid accumulations. Scanning electron microscopic examination of control group sections presented regular endothelial topography, while carotid bifurcation region topography exhibited numerous blood cells and separated endothelial cells. Fibrin accumulation on endothelial surface in low area ratios was another important finding in the examination of its endothelial surface degeneration. The above-mentioned morphological findings seemed to be quite parallel to outflow to inflow area ratio data favouring low area and degeneration. Conclusion: The correlation between area ratios and the histological characteristic of cerebral vessels of newborn cadavers indicate that early stages of atherosclerosis began in early embryologic life.
Keywords: Carotid artery; Cerebral blood flow; Cerebral haemodynamics; Endothelium; BALLOON AORTIC VALVULOPLASTY; RISK-FACTOR; ARTERY; GEOMETRY; ANATOMY; HYPERCHOLESTEROLEMIA; DIAMETERS